2008
DOI: 10.1109/temc.2008.926880
|View full text |Cite
|
Sign up to set email alerts
|

Path Loss From a Transmitter Inside an Aircraft Cabin to an Exterior Fuselage-Mounted Antenna

Abstract: Abstract-The increasing use of mobile electronic devices by passengers and equipment on large aircraft may increase the likelihood of interference with the aircraft's electronic systems. Thus, the "interference path loss" from a transmitting device inside the cabin of such aircraft to the antenna terminals of a victim system of the aircraft is of interest. Full-wave modeling and other deterministic techniques are impractical or undesirable for this purpose due to the potentially large electrical dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Power absorption in bodies can be easily combined with other losses, such as in the passenger seats in an airliner [5]. The absorption effect applies not only in aircraft [6,7] but also in other confined spaces such as tunnels and mines [8].…”
Section: Introductionmentioning
confidence: 99%
“…Power absorption in bodies can be easily combined with other losses, such as in the passenger seats in an airliner [5]. The absorption effect applies not only in aircraft [6,7] but also in other confined spaces such as tunnels and mines [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, ray tracing has been employed for site-specific indoor propagation models [1][2][3], and it has been shown that multiple reflections are dominant for the RF field build-up within the cavity compared to the phenomenon of diffraction [4]. Although ray tracing has been used earlier for electromagnetic (EM) analysis of aircraft cabin-like enclosures, a closer scrutiny reveals that these predominantly employ measurements to merely fit their predictions or to validate their empirical models [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the adaptation of wireless communication inside aircraft is not straight forward, as the available technologies pose critical electromagnetic interference (EMI) issues [2]. This is evermore so, since safety of a commercial aircraft can only be guaranteed whilst preserving the integrity of the aircraft's communications and control equipment [3]. The past years have thus attested escalated concerns for the penetration of high-intensity radiated fields (HIRF) into conducting enclosures, particularly after a number of aviation incidents have been attributed to the disruption of communications or loss of accuracy of the navigation equipment [4].…”
Section: Introductionmentioning
confidence: 99%